RADT-40. TRENDS IN THE USE OF RADIATION FOR MENINGIOMA ACROSS THE UNITED STATES. (9th November 2020) - Matani, Hirsch; Abel, Stephen; Xu, Linda; Yu, Alexander; Ranjan, Tulika; Karlovits, Stephen; Wegner, Rodney
Abstract: BACKGROUND: Meningiomas are tumors originating from arachnoid cap cells on the surface of the brain or spinal cord. Treatment differs by grade but can consist of surgery, radiation therapy or both. We utilized the national cancer database (NCDB) to compare trends in the use stereotactic radiosurgery (SRS) and external beam radiation therapy (EBRT) in the management of meningioma. METHODS: We queried the NCDB from 2004-15 for meningioma patients (Grade 1-3) treated with radiation therapy, either SRS or EBRT. Multivariable logistic regression was used to identify predictors of each treatment and to generate a propensity score. Propensity adjusted Kaplan-Meier survival curve analysis and multivariable cox hazards ratios were used to identify predictors of survival. RESULTS: We identified 5406 patients with meningioma meeting above criteria. Median follow up was 43 months. 45%, 44%, and 11% were Grade 1, 2, and 3, respectively. Predictors for SRS were distance from treatment facility and histology. Predictors of EBRT were tumor size and WHO grade 2 or 3 disease. Tumor size, treatment year, and receipt of chemotherapy were associated with improved survival. Five and ten year survival rates were 89.2% vs. 72.6% (p < 0.0001) and 80.3% vs. 61.4% (p = 0.29) for SRS and EBRT respectively. After propensity matching 226 pairs were generated. For SRS, 5 year survival was not significantly improved at 88.2% (p = 0.056) CONCLUSIONS: In the present analysis, predictors of SRS utilization in management of meningioma include distance from treatment facility and histology whereas conventional EBRT utilization was associated with tumor size and grade 2 or 3 disease. Despite a possible survival benefit with SRS, inherent selection bias may confound interpretation of the apparent survival benefit reflected in our study.